On the geometry of the ambiguity search space with and without the ionosphere. - Teunissen, Peter (1996)
The size and shape of the ambiguity search space is instrumental for estimation and validation of the integer GPS ambiguities. A qualitative analysis based on analytical formulae will be given of the geometry of the ambiguity search space. This will be done for the case the ionosphere is assumed to be present, as well as for the case the ionosphere is assumed to be absent. It is also shown to what extent the statistics of the ambiguities, can be improved by means of the Least-squares AMBiguity Decorrelation Adjustment (LAMBDA) method.